Information disparity : research and measurement challenges in an interconnected world - Boyd, Andrew, 1956- (Aslib proceedings, 2004)
With the proliferation of new information channels such as the Web, e-mail and wireless, it is becoming increasingly important to understand the impact of these technologies within information-seeking and retrieval contexts. In many instances information seeking and retrieval is an ad hoc activity and supporting information systems (either personal or organisational) are generally not designed to optimise information sharing. Previously published in: Aslib Proceedings, Volume 56, Number 5, 2004.